Irregular frequency elimination of three-dimensional hydroelasticity in frequency domain. (15th January 2020) - Yang, Peng; Li, Jingru; Wu, Dongwei; Zhang, Wei
Abstract: The irregular frequencies affect the analysis of hydroelastic responses and wave loading of the floating structures, such as springing and whipping. In numerical prediction, the responses are likely to be overestimated. The theoretical basis of three-dimensional hydroelasticity for removing irregular frequencies in infinite and finite water depths is formed by a boundary integral method and adding a rigid lid to free surface of the inner fluid zone. One barge and one bulk carrier are taken as research objects for validating the feasibility of method for hydroelasticity and investigating the influence of the irregular frequency on hydrodynamic coefficients, diffraction forces and hydroelastic responses. The effectiveness of the method and mesh of the rigid lid are assessed. The method adopted in the paper could efficiently eliminate the irregular frequency for infinite and finite water depths. The irregular frequencies should be eliminated in a hydroelastic response assessment, especially for the large floating structures. Highlights: The method of removing irregular frequencies in hydroelasticity is adding a rigid lid. The feasibility of the adopted method in hydroelasticity is validated. The effectiveness of the method and mesh of the rigid lid are assessed.